Policing in the Media Arena: Layered Accountability and Oversight in Reality Police Shows - Artasasta Tambunan, Daniel; Suparwati, Kadek Citra Dewi; Sembiring Meliala, Adrianus Eliasta; Supardi Hamid; Ilham Prisgunanto (Jurnal Ilmu Kepolisian, 2026)
This article examines how mediated visibility reconfigures police oversight and accountability in Indonesia by treating reality police shows as an empirical arena. This study uses a qualitative–analytical design integrating semi-structured interviews with key institutional actors (Indonesian National Police/POLRI, media practitioners, and broadcast regulators), observational analysis of televised police representations and the digital recirculation, and document analysis of relevant governance and communication frameworks. The findings show that formal oversight mechanisms within Polri and state-based supervisory arrangements tend to operate reactively and with temporal delay when faced with fast-moving, visually driven public scrutiny. In this gap, media platforms, through televised programs and fragmented online circulation, function as a dominant informal overseer that shapes public judgments through visibility management, framing, and affective resonance. These dynamics generate an asymmetrical layered accountability regime, in which symbolic accountability formed in the media arena frequently precedes and constrains the operation of formal accountability processes. The article further identifies a condition of dual accountability that produces a structural dilemma for the Public Relations Division of POLRI (Divhumas), which must uphold law-based procedural legitimacy while simultaneously responding to media-generated demands for symbolic legitimacy. Limited post-production evaluation, weak coordination across the production cycle, and crisis-oriented communication approaches shift meaning-making power toward media actors and audiences, increasing institutional vulnerability to representational distortion. The article contributes to Police Science by conceptualizing accountability as a cross-arena governance process and by outlining policy implications for strategic visibility management, preventive representational oversight, and early-warning monitoring of legitimacy risk under conditions of mediated policing.